2016
DOI: 10.1136/vr.103844
|View full text |Cite
|
Sign up to set email alerts
|

Higher perceived risks of antimicrobial use are related to lower usage among pig farmers in four European countries

Abstract: The prudent use of antimicrobials (AMs) should be widened in pig farming to reduce the risk of AM resistance (AMR) in human and veterinary medicine. It is therefore important to understand pig farmers' motivators and the barriers to AM usage (AMU) on their farms. The authors investigated pig farmers' self-estimated levels of AMU, their perceived benefits and risks and the need for AMs in a cross-sectional survey in Belgium, France, Germany and Sweden. The authors also compared these perceptions between the fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 22 publications
3
29
0
2
Order By: Relevance
“…To the authors' knowledge, ours is the first study of the enablers of and barriers to AMS in veterinary practice although several studies have examined attitudes and knowledge about AMR and the impact of antibiotic use. [18][19][20] Our results show that 89% of the veterinarians who responded to the questionnaire self-reported that they would support AMS programs in their practices and that limiting factors commonly involve pressure from clients to dispense antimicrobials. This finding is in contrast to a survey of factors influencing prescribing in European veterinarians, where owner demands were among the least important factors.…”
Section: Discussionmentioning
confidence: 82%
“…To the authors' knowledge, ours is the first study of the enablers of and barriers to AMS in veterinary practice although several studies have examined attitudes and knowledge about AMR and the impact of antibiotic use. [18][19][20] Our results show that 89% of the veterinarians who responded to the questionnaire self-reported that they would support AMS programs in their practices and that limiting factors commonly involve pressure from clients to dispense antimicrobials. This finding is in contrast to a survey of factors influencing prescribing in European veterinarians, where owner demands were among the least important factors.…”
Section: Discussionmentioning
confidence: 82%
“…Une autre série d' études a reposé sur une approche quantitative, à partir d' études épidémiologiques investiguant entre autres des facteurs relatifs aux traits de personnalités, aux perceptions, au niveau de revenu des éleveurs, ainsi qu'à leur ressenti sur les approches de réduction d'usage des antibiotiques (Le Bouquin et al, 2013 ;Visschers et al, 2015 ;Visschers et al, 2016a ;Visschers et al, 2016b ;Rousset et al, 2018). Une d' entre elles est une étude d'intervention conduite dans quatre pays européens (Collineau et al, 2017).…”
Section: Facteurs Influençant L'observance Par L'éleveur De Changemenunclassified
“…En filière porcine, des études conduites conjointement dans quatre pays européens (Allemagne, Belgique, France, Suède) et centrées sur la perception qu'ont les éleveurs des antibiotiques ont montré l'existence de nombreux traits communs entre les pays, et analysé l'influence des facteurs extrinsèques (Visschers et al, 2015 ;Visschers et al, 2016a ;Visschers et al, 2016b). Les résultats soulignent la mauvaise perception par les éleveurs des contraintes règlementaires ou des pénalités financières (qui s'appliqueraient à de forts utilisateurs) comme levier de modification des usages ; ils perçoivent mieux l'accompagnement par le vétérinaire, les incitations financières (bonus, primes) et les démarches volontaires.…”
Section: Facteurs Influençant L'observance Par L'éleveur De Changemenunclassified
“…Consequently, a series of studies were performed to analyze the cognitive and behavioral barriers to the appropriate use of antimicrobials by various stakeholders in the livestock sector. Previous studies highlighted farmers' lack of knowledge about antimicrobials and AMR ( 20 , 21 ), showing that while farmers were fairly unconcerned about the risks associated with AMR, they perceived many benefits from their use ( 20 , 22 , 23 ). Other works have shed light on the thought processes of field actors while choosing whether or not to use antimicrobials.…”
Section: Introductionmentioning
confidence: 99%